Recent progress on natural fiber hybrid composites for advanced applications: A review - M. J. Mochane; T. C. Mokhena; T. H. Mokhothu; A. Mtibe; E. R. Sadiku; S. S. Ray; I. D. Ibrahim; O. O. Daramola (eXPRESS Polymer Letters, 2019)
Natural fibers, as replacement of engineered fibers, have been one of the most researched topics over the past years. This is due to their inherent properties, such as biodegradability, renewability and their abundant availability when compared to synthetic fibers. Synthetic fibers derived from finite resources (fossil fuels) and are thus, affected mainly by volatility oil prices and their accumulation in the environment and/or landfill sites as main drawbacks their mechanical properties and thermal properties surpass that of natural fibers. A combination of these fibers/fillers, as reinforcement of various polymeric materials, offers new opportunities to produce multifunctional materials and structures for advanced applications. This article intends to cover recent developments from 2013-up to date on hybrid composites, based on natural fibers with other fillers. Hybrid composites preparation and characterization towards their applicability in advanced applications and the current challenges are also presented.